Upaya Meningkatkan Kecerdasan Kinestetik Melalui Metode Bermain Peran di PAUD Syarah - Fauziah Nasution; Evi sukmapratiwi; Miftahul Jannah Harahap; Novia Rahmawati (CV Edujavare Publishing, 2025)
This study was conducted to explore efforts to improve kinesthetic intelligence in preschool children through the application of drama methods in PAUD Syarah. Kinesthetic intelligence can be interpreted as a child's ability to optimally utilize his body to convey ideas and emotions, as well as including fine and gross motor skills. The research approach applied was Classroom Action Research (CAR), which was implemented in two cycles, with 15 children from group B as research objects. Data collection was carried out through observation, document collection, and interviews. The research findings indicate that the application of structured and planned role-playing methods can encourage an increase in children's kinesthetic intelligence. This can be seen from the increase in children's ability to imitate movements, regulate body coordination, and active involvement in role-playing activities. The conclusion of this study is that the drama method is proven to be effective as a learning strategy to advance the kinesthetic intelligence of early childhood children in PAUD Syarah.